A hope springs christmas ebook - Davids, Patricia (Brides of Amish Country., 2023)
USA Today –Bestselling Author: Two selfless, heart-filled souls help one another find love in this Amish romance. Amish widow Sarah Wyse does not see wedding bells in her future. Still, she can't think of a better way to spend the Christmas season than helping her handsome, shy neighbor Levi Beachy find a wife. But once the single ladies of Hope Springs start visiting his buggy shop, Levi sends the town's eligible men Sarah's way. Neither expects to find love—but with help from the close-knit community, they just might mend each other's broken heart. Brides of Amish Country The Amish Innkeeper's Secret Katie's Redemption The Doctor's Blessing An Amish Christmas The Farmer Next Door The Christmas Quilt A Home for Hannah A Hope Springs Christmas Plain Admirer Amish Christmas Joy The Shepherd's Bride The Amish Nanny An Amish Christmas Journey Amish Redemption